Three new genera and three new species of Nearctic Lasiopteridi (Diptera: Cecidomyiidae: Cecidomyiinae) from Asteraceae and Caprifoliaceae, and the tribe Rhopalomyiini subsumed under Oligotrophini - Gagné, Raymond J. (Zootaxa, 2016)
Three new Nearctic genera of gall midges (Diptera: Cecidomyiidae), each with a new species, are described: Helianthecis Gagné for Helianthecis capitum Gagné, new species, that lives in flower heads of Helianthus spp. (Asteraceae) from North Dakota to Texas; Lonicerae Gagné for Lonicerae russoi Gagné, new species, and Lonicerae lonicera (Felt), new combination, that form bud galls on Lonicera spp. (Caprifoliaceae) in California; and Chiosperma Gagné for Chiosperma turgidum Gagné, new species, that forms a bud gall on Symphoricarpos albus (L.) S.F. Blake (Caprifoliaceae) in Washington. The three new genera belong to the supertribe Lasiopteridi and are placed in the tribe Oligotrophini. The tribes Oligotrophini and Rhopalomyiini are combined.